A Stat6/Pten Axis Links Regulatory T Cells with Adipose Tissue Function - Kaelin, Stefanie; Becker, Maike; Ott, Verena B.; Serr, Isabelle; Hosp, Fabian; Mollah, Mohammad M. H.; Keipert, Susanne; Lamp, Daniel; Rohner-Jeanrenaud, Francoise; Flynn, Victoria K.; Scherm, Martin G.; Nascimento, Lucas F. R.; et al. (Cell Metabolism, 2017)
Obesity and type 2 diabetes are associated with metabolic defects and adipose tissue inflammation. Foxp3+ regulatory T cells (Tregs) control tissue homeostasis by counteracting local inflammation. However, if and how T cells interlink environmental influences with adipocyte function remains unknown. Here, we report that enhancing sympathetic tone by cold exposure, beta3-adrenergic receptor (ADRB3) stimulation or a short-term high-calorie diet enhances Treg induction in vitro and in vivo. CD4+ T cell proteomes revealed higher expression of Foxp3 regulatory networks in response to cold or ADRB3 stimulation in vivo reflecting Treg induction. Specifically, Ragulator-interacting protein C17orf59, which limits mTORC1 activity, was upregulated in CD4+ T cells by either ADRB3 stimulation or cold exposure, suggesting contribution to Treg induction. By loss- and gain-of-function studies, including Treg depletion and transfers in vivo, we demonstrated that a T cell-specific Stat6/Pten axis links cold exposure or ADRB3 stimulation with Foxp3+ Treg induction and adipose tissue function. Our findings offer a new mechanistic model in which tissue-specific Tregs maintain adipose tissue function.
EVALuna2:33893